Adenomyoepitheliomas of the Breast Frequently Harbor Recurrent Hotspot Mutations in PIK3-AKT Pathway-related Genes and a Subset Show Genetic Similarity to Salivary Gland Epithelial-Myoepithelial Carcinoma. (July 2019) - Lubin, Daniel; Toorens, Erik; Zhang, Paul J.; Jaffer, Shabnam; Baraban, Ezra; Bleiweiss, Ira J.; Nayak, Anupma
Abstract : Adenomyoepitheliomas (AME) of the breast and epithelial-myoepithelial carcinomas (EMCs) of salivary gland are morphologically similar tumors defined by the presence of a biphasic population of ductal epithelial elements mixed with myoepithelial cells. We sought to explore the molecular profile of AMEs and determine whether they might also share the PLAG1, HMGA2, and HRAS alterations seen in EMCs. Tumor tissue from 19 AMEs was sequenced and analyzed using Ion AmpliSeq Cancer Hotspot Panel v2 covering ∼2800 COSMIC mutations across 50 cancer-related genes. Cases were additionally screened by FISH for PLAG1 and HMGA2 rearrangements. Of 19 AMEs (12 benign; 7 malignant), 2 cases failed the DNA extraction. Of the remaining 17 cases, 14 had at least one nonsynonymous mutation identified. The most common mutations were in PIK3CA (6/17) and AKT1 (5/17), which were mutually exclusive. Two tumors demonstrated mutations in APC, while 1 demonstrated an STK11 mutation. Mutations in ATM, EGFR, FGFR3 or GNAS were identified in 4 cases with concurrent AKT1 mutations. HRAS mutation co-occurring with PIK3CA mutation was noted in 1 case of ER-negative malignant AME. While 2 cases harbored alterations in HMGA2, none was positive for PLAG1 rearrangement. Our findings confirm that breast AMEs are genetically heterogeneous exhibiting recurrent mutually exclusive mutations of PIK3CA and AKT1 in a majority of cases. HRAS mutations co-occur with PIK3CA mutations in ER-negative AMEs and may possibly be linked to clinically aggressive behavior. We identified hotspot mutations in additional genes ( APC, STK11, ATM, EGFR, FGFR3, and GNAS ). We report the presence of HMGA2 alterations in 2/16 AMEs, supporting their relationship with EMC of salivary glands in at least a subset of cases. PIK3CA, AKT1 and HRAS may serve as potential actionable therapeutic targets in clinically aggressive AMEs.